2000
DOI: 10.1002/j.1552-4604.2000.tb05992.x
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Does Not Significantly Alter the Pharmacokinetics or Hypoprothrombinemic Effect of Warfarin in Healthy Subjects

Abstract: The objective of this study was to determine the effects of celecoxib, an anti-inflammatory/analgesic agent that primarily inhibits COX-2 and not COX-1 at therapeutic doses, on the steady-state pharmacokinetic profile and hypoprothrombinemic effect of racemic warfarin in healthy volunteers. Twenty-four healthy adult volunteers on maintenance doses of racemic warfarin (2-5 mg daily), stabilized to prothrombin times (PT) 1.2 to 1.7 times pretreatment PT values for 3 consecutive days, were randomized to receive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The typical example is the celecoxib-warfarin interaction. The manufacturer had concluded no interaction with warfarin by performing open-label, multi-dose, placebo-controlled randomized study performed on 24 healthy volunteers (Karim et al 2000). However, after its introduction to market, a few case reports began to emerge about clinically significant delays in INR (Mersfelder and Stewart 1997;Haase et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The typical example is the celecoxib-warfarin interaction. The manufacturer had concluded no interaction with warfarin by performing open-label, multi-dose, placebo-controlled randomized study performed on 24 healthy volunteers (Karim et al 2000). However, after its introduction to market, a few case reports began to emerge about clinically significant delays in INR (Mersfelder and Stewart 1997;Haase et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Celecoxib and rofecoxib are recently marketed NSAIDs that are reported 19,20 to have no significant effects on bleeding time or platelet aggregation. Initial product labeling 21 for celecoxib reported that a drug interaction study in healthy volunteers showed that the drug did not alter the anticoagulant effects of warfarin.…”
mentioning
confidence: 99%
“…This observation should represent a possible mechanism for how a drug interaction may be elicited in the drug metabolizing system. However, in this particular observation this has to be further elucidated, since the warfarin-celecoxib interaction was not seen in healthy volunteers (Karim et al 2000).…”
Section: Impact Of Non-functional Alleles On Drug-drug-interactionmentioning
confidence: 89%